Credit Restructuring by Bali Regional Development Bank to Debtors During the Covid-19 Pandemic - Putu Ayu Sriasih Wesna; Ida Bagus Kade Ari Dwi Putra; I Nyoman Sujana (Warmadewa Press, 2023)
Restructuring credit serves as a strategic avenue to ameliorate the financial status of businesses facing adversity, especially those entwined with creditor banks, to assist struggling debtors in meeting their obligations. This study delves into the restructuring initiatives undertaken by BPD Bali amid the Covid-19 pandemic, scrutinizing the associated legal implications. This research uses empirical legal research methodology, using a qualitative approach. The data collection techniques used in this research are in-depth interviews, observation, and document analysis. Data obtained from interviews, observations, and document analysis will be analyzed qualitatively. Qualitative analysis is carried out by interpreting the data in depth and thoroughly to produce meaningful conclusions. The result of this study show that the Bali Regional Development Bank's approach involved a meticulous assessment of debtors' integrity and reliability, prioritizing trustworthy customers for credit restructuring. Specifically, for loans ranging from fifty million to five hundred million, the bank adopted reconditioning and rescheduling techniques. The repercussions for debtors entailed a modification in the original agreement with the bank, resulting in the nullification of the initial credit terms initially committed to by both the creditor and debtor.